Pengaruh Zakat, Infaq, dan Indeks Pembangunan Manusia (IPM) Terhadap Pengentasan Kemiskinan di Indonesia Periode 2019-2023 - Dwike Yuniar Wina Nisfulaili; Desi Oktaviani; Frendi Alpiliano (DPPM Universitas Pelita Bangsa, 2025)
This study aims to analyze the effect of zakat, infaq, and the Human Development Index (HDI) on poverty levels in Indonesia in 2019 2023. This study uses a quantitative approach with the panel data method and the Fixed Effect Model (FEM) model. The data used is secondary data from 34 provinces in Indonesia. The results showed that the zakat and infaq variables had no significant effect on poverty, although both had a positive relationship direction. This shows that the increase in zakat and infaq has not impacted poverty reduction, possibly due to non-optimal management and consumptive distribution patterns. Meanwhile, the HDI variable has a negative and significant effect on poverty, which means that improving the quality of education, health, and living standards can significantly reduce the poverty rate.